Effects of different types of radiation therapy on cardiac-specific death in patients with thyroid malignancy - Wang, Ruxin; Ye, Haowen; Wang, Ying; Ma, Li; Wei, Jinjing; Zhang, Xiaofang; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Radiation therapy (RT) is one of the common and widely used treatment method for thyroid tumors, considering that the thyroid is located close to the heart, the radiation generated during the treatment of thyroid tumors may have an adverse greater impact on the heart. This study is to explore the influencing factors, especially additional effects of RT, on death of heart disease among patients with thyroid malignant tumors by mining information from clinical public databases. The SEER database was accessed using SEER*Stat version 8.4.0.1, and the database was searched for patients with thyroid malignant tumors, whether receiving RT or not. Those who were unsure whether to receive RT were excluded, ultimately, 201, 346 eligible patients were included. Propensity Score Matching (PMS) was used to minimize bias of baseline characteristics, COX (Proportional Hazards) and Fine-Gray (Competing Risk) model regression analysis were used to explore the effects of various influencing factors on death of heart disease among patients with thyroid malignant tumors. Multivariate COX regression analysis showed that RT (radioisotopes, radioactive implants, and beam radiation) had obvious protective effect in reducing death of heart disease, in addition, Asian or Pacific Islander, female, married, combined summary stage (localized, regional, distant), year of diagnosis (later), and histologic type (8020-8029) were protective factors in reducing death of heart disease; Age of diagnosis, race, non-Hispanic, derived AJCC stage (Ⅳ), and histologic type (8050-8059 ) were risk factors in increasing death of heart disease. These results help to identify the influencing factors of death of heart disease among patients with thyroid malignancies so as to give corresponding preventive measures, and improve the clinical application of RT in thyroid malignancies without too much concern about adverse cardiac effects.